2017
DOI: 10.1007/s00248-017-0997-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bufadienolides from the Boreal Toad, Anaxyrus boreas, Active Against a Fungal Pathogen

Abstract: Amphibian granular glands provide a wide range of compounds on the skin that defend against pathogens and predators. We identified three bufadienolides-the steroid-like compounds arenobufagin, gamabufotalin, and telocinobufagin-from the boreal toad, Anaxyrus boreas, through liquid chromatography mass spectrometry (LC/MS). Compounds were detected both after inducing skin gland secretions and in constitutive mucosal rinses from toads. We described the antimicrobial properties of each bufadienolide against Batrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 79 publications
0
36
1
Order By: Relevance
“…The authors indicated that this compound modulated human innate immune responses and triggered antibacterial activity. Arenobufagin and gamabufotalin also exhibited antimicrobial properties (Barnhart et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The authors indicated that this compound modulated human innate immune responses and triggered antibacterial activity. Arenobufagin and gamabufotalin also exhibited antimicrobial properties (Barnhart et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Both NBC and TBQ were correlated with one or two NMDS axes describing the bacterial community of larval habitats. This may be a cause-effect relationship, because bufadienolides can have antipathogenic and antiparasitic effects (Barnhart et al 2017;Cunha Filho et al 2005;Tempone et al 2008), and Bufonid toads lack AMP-s (Conlon 2011;König et al 2015), therefore the involvement of bufadienolides in skin-based immune-defense is probable, and their synthesis may be adjusted to the presence or absence of particular pathogens or specific members of bacterial communities. The presence of certain bacteria and changes in the natural microbiota can induce responses in chemical defenses (up-or down-regulation of AMP synthesis) in adult frogs (Mangoni et al 2001;Miele et al 1998;Simmaco et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Several toad species in the family Bufonidae are known to synthesize bufadienolides de novo in the serous glands of their skin already from early larval stages on (Hayes et al 2009a;Ujszegi et al 2017;Üveges et al 2017). These skin-toxins may be effective against natural enemies including predators (Denton and Beebee 1991;Hantak et al 2016;Kruse and Stone 1984;Peterson and Blaustein 1991;Shine 2010), competitors (Bókony et al 2018) and potential pathogens (Barnhart et al 2017;Cunha Filho et al 2005;De Medeiros et al 2019;Tempone et al 2008). However, little is known about what evolutionary processes and environmental factors influence bufadienolide synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bufadienolides are produced in parotid glands and the skin of a toad [2]. These toxic compounds are potent inhibitors of Na + /K + -ATPase activity, and toads use these as a natural repellent against predators and also as an immune defence against pathogens [3,4]. Bufadienolides are divided into bufagenins, the smaller, hydrolysed molecules which have stronger cardiotoxic effects, and bufotoxins, the larger bufadienolide molecules with an amino-acid side chain [5].…”
Section: Introductionmentioning
confidence: 99%